Pengembangan Metode Analisis Penetapan Zat Warna Merah K3 pada Produk Eyeshadow Menggunakan Spektrofotometri UV-Visible dengan Pemisahan Ekstraksi Fase Padat - Rismaya Desti Parwati; Anggi Gumilar; Muhammad Naufal Dhiaulhaq (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2026)
The use of synthetic dyes such as Red K3 in cosmetics is prohibited due to its carcinogenic and toxic properties. However, this dye is still found in several eyeshadow products sold via e-commerce. This study aims to develop and validate a UV-Visible spectrophotometric method combined with Solid Phase Extraction (SPE) to identify and quantify Red K3 in eyeshadow. Method validation was performed by evaluating parameters including accuracy, precision, selectivity, linearity, and range. The validation results showed an accuracy of 99.970% and a precision of 1.571% RSD, both meeting the acceptance criteria. The calibration curve showed a linear relationship with a correlation coefficient (r) of 0.9986. The method used demonstrated good sensitivity, as indicated by the limit of detection (LOD) value of 0.657 µg/mL and the limit of quantification (LOQ) value of 2.190 µg/mL. Among 10 eyeshadow samples from e-commerce, only 1 sample (Sample C) was identified to contain Red K3. The developed method is valid and suitable for cosmetic safety monitoring, especially for products sold online.